Academic Engagement as a Driver of Institutional Capabilities: Evidence from the Knowledge, Innovation, and Collaboration Pathways - Hari Moektiwibowo; Hapzi Ali (Dinasti International Journal of Digital Business Management, 2026)
This study aims to develop a conceptual model explaining how academic engagement contributes to the development of dynamic capabilities in higher education institutions in Asia through internal capability mechanisms. The research adopts a literature review design using a semi-systematic approach to integrate diverse theoretical perspectives. The data consist of peer-reviewed academic articles analyzed through thematic synthesis to identify patterns and relationships among variables. The findings indicate that academic engagement contributes indirectly to dynamic capabilities through three key mediating capabilities, namely knowledge creation, innovation capability, and research collaboration. These capabilities operate as an integrated system that enhances institutional adaptability and competitiveness. However, the existing literature remains fragmented and tends to examine these capabilities in isolation, limiting a comprehensive understanding of their interrelationships. This study provides conceptual implications for developing an integrated capability-based model and recommends further empirical testing by incorporating digital transformation and institutional context variability